Time Use in Economic and Social Accounts, 1975-1976 - Juster, F. Thomas ([Verlag nicht ermittelbar], 1984)
This data collection represents an attempt to apply recent methodological developments in the measurement of time use to a national probability sample of United States households in order to facilitate development of a fully articulated system of economic and social accounts. The data for this study were collected from a sample of 2,406 adults (1,519 respondents and 887 spouses) first interviewed in October-November 1975, and reinterviewed three more times in February, May, and September 1976. Respondents were asked to keep a diary of daily activities so that time allocation patterns could be estimated for the entire year. In addition to the basic estimates of time use obtained from the diaries, the four waves of interviewing obtained information on the employment status of the respondent and spouse, the earnings and other income of the respondent and spouse, the "consumption benefits" for activities engaged in, the health, friendships, and associations of the respondents, the stock of technology available to the household, the house repair and maintenance activities of the family, the division of labor in household work and related attitudes, the physical characteristics of the respondents' housing structure, net worth and housing values, the job characteristics of the respondent and spouse, and the characteristics of mass media usage on a typical day. Background variables include marital status, education, religion, and political preference. AMERICAN'S USE OF TIME, 1965-1976, AND TIME USE IN ECONOMIC AND SOCIAL ACCOUNTS, 1975-1976: MERGED DATA (ICPSR 7796) is a data collection that combines this study with a similar one.